Overview of the Budapest convention on cybercrime - Zulhuda, Sonny (2014)
The challenges of the digitalisation, convergence and globalisation of computer networks give rise to the risk that computer networks and electronic information may be used for committing criminal offences and storing related evidences. The discussion on the importance of Budapest Convention on Cybercrime in Malaysian context becomes increasingly important due to the need for co-operation between States and private industry in combating cybercrime. There is also a need to protect legitimate interests in the use of information technologies; as well as a need for an increased, rapid and well-functioning international co-operation in cyber criminal matters. Malaysia needs to have a strong cybercrime legal regime in order to avoid becoming a safe haven for cyber criminals.